Wire like diplatinum, triplatinum, and tetraplatinum complexes featuring X[PtCCCCCCCC]mPtX segments; Iterative syntheses and functionalization for measurements of single molecule properties - Zheng, Qinglin; Schneider, Jakob F.; Amini, Hashem; Hampel, Frank; Gladysz, John A. (Dalton Transactions, 2019)
Reaction of (p-tol 3 P) 2 PtCl 2 and Me 3 Sn(CC) 2 SiMe 3 (1:1/THF/reflux) gives monosubstituted trans-Cl(p-tol 3 P) 2 Pt(CC) 2 SiMe 3 (63%), which with wet n-Bu 4 N + F - yields trans-Cl(p-tol 3 P) 2 Pt(CC) 2 H (2, 96%). Hay oxidative homocoupling (O 2 /CuCl/TMEDA) gives all-trans-Cl(p-tol 3 P) 2 Pt(CC) 4 Pt(Pp-tol 3 ) 2 Cl (3, 68%). Reaction of 3 and Me 3 Sn(CC) 2 SiMe 3 (1:1/rt) affords monosubstituted all-trans-Cl(p-tol 3 P) 2 Pt(CC) 4 Pt(Pp-tol 3 ) 2 (CC) 2 SiMe 3 (46%), which is converted by a similar desilylation/homocoupling sequence to all-trans-Cl[(p-tol 3 P) 2 Pt(CC) 4 ] 3 Pt(Pp-tol 3 ) 2 Cl (7; 79%). Reaction of (p-tol 3 P) 2 PtCl 2 and excess H(CC) 2 SiMe 3 (HNEt 2 /cat. CuI) gives trans-Me 3 Si(CC) 2 Pt(Pp-tol 3 ) 2 (CC) 2 SiMe 3 (78%), which with wet n-Bu 4 N + F - affords trans-H(CC) 2 Pt(Pp-tol 3 ) 2 (CC) 2 H (96%). Hay oxidative cross coupling with 2 (1:4) gives all-trans-Cl[(p-tol 3 P) 2 Pt(CC) 4 ] 2 Pt(Pp-tol 3 ) 2 Cl (10, 36%) along with homocoupling product 3 (33%). Reaction of 3 and Me 3 Sn(CC) 2 SiMe 3 (1:2/rt) yields all-trans-Me 3 Si(CC) 2 (p-tol 3 P) 2 Pt(CC) 4 Pt(Pp-tol 3 ) 2 (CC) 2 SiMe 3 (17, 77%), which with wet n-Bu 4 N + F - gives all-trans-H(CC) 2 (p-tol 3 P) 2 Pt(CC) 4 Pt(Pp-tol 3 ) 2 (CC) 2 H (96%). Reaction of 3 and excess Me 3 P gives all-trans-Cl(Me 3 P) 2 Pt(CC) 4 Pt(PMe 3 ) 2 Cl (4, 86%). A model reaction of trans-(p-tol)(p-tol 3 P) 2 PtCl and KSAc yields trans-(p-tol)(p-tol 3 P) 2 PtSAc (12, 75%). Similar reactions of 3, 7, 10, and 4 give all-trans-AcS[(R 3 P) 2 Pt(CC) 4 ] n Pt(PR 3 ) 2 SAc (76-91%). The crystal structures of 3, 17, and 12 are determined. The first exhibits a chlorine-chlorine distance of 17.42 Å; those in 10 and 7 are estimated as 30.3 Å and 43.1 Å.
CRIS-Team Scopus Importer:2019-05-14